An Integrated Cytoskeletal Model of Neurite Outgrowth - Miller, Kyle E.; Suter, Daniel M. (Frontiers in Cellular Neuroscience, 2018)
Understanding neurite outgrowth is important because it underlies the wiring of the nervous system during development and regeneration following trauma and disease. Despite a significant body of research, the underlying cytoskeletal and mechanical mechanisms of growth and guidance are still not fully understood. Here, we bring together quantitative data to develop an integrated mechanical model of axonal elongation. The strength of this approach is that by focusing on forces rather than individual processes in a quantitative framework, the relative contributions of different processes to neurite growth can be impartially considered. We begin this review by discussing the structural organization of neurons focusing on the actin and microtubule (MT) cytoskeletons. Then, recent studies on the biophysics of growth cones and axons are covered to develop a more integrated model of neurite growth. With this foundation, some of the “controversial” findings in this field are discussed. A central idea that develops is that neurons appear to be active fluids, which generate strong contractile forces in the growth cone and weaker contractile forces along the axon. As a result of subcellular gradients in forces and material properties, actin flows rapidly rearwards in the growth cone periphery and MTs flow forward in bulk along the axon. From this a picture emerges that a growth cone is much like a migrating cell coupled to the cell body by the axon. Forces and cytoskeletal dynamics in the growth cone control its advance, whereas the axon acts to restrain and support growth cone motility. The major difference of the present integrated model to previous models is that the growth cone moves forward as a coherent structure and pulls the adjacent axon along, instead of advancing by the assembly of MTs at the tip of the axon. With this perspective, new approaches for promoting neuronal regeneration are discussed.